Corticosteroids as adjunctive therapy in the treatment of influenza - Rodrigo, Chamira; Leonardi-Bee, Jo; Nguyen-Van-Tam, Jonathan; Lim, Wei Shen (Wiley, 2016)
Background: Specific treatments for influenza are limited to neuraminidase inhibitors and adamantanes. Corticosteroids show evidence of benefit in sepsis and related conditions, most likely due to their anti-inflammatory and immunomodulatory properties. Although commonly prescribed for severe influenza, there is uncertainty over their potential benefit or harm.